1990
DOI: 10.1136/bmj.301.6755.783
|View full text |Cite
|
Sign up to set email alerts
|

Unawareness of hypoglycaemia and inadequate hypoglycaemic counterregulation: no causal relation with diabetic autonomic neuropathy.

Abstract: Objective-To examine the traditional view that unawareness of hypoglycaemia and inadequate hypoglycaemic counterregulation in insulin dependent diabetes meilitus are manifestations of autonomic neuropathy.Design-Perspective assessment of unawareness of hypoglycaemia and detailed assessment of autonomic neuropathy in patients with insulin dependent diabetes according to the adequacy of their hypoglycaemic counterregulation.Setting-One routine diabetic unit in a university teaching hospital. IntroductionUnaware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…It is associated with a failure of the normal counterregulatory mechanisms that alert the diabetic patient to a falling blood glucose concentration (4). Most notably, the onset of the catecholamine and sympathetic responses to hypoglycemia is significantly delayed, with reduced magnitude of these responses at any given glucose level (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with a failure of the normal counterregulatory mechanisms that alert the diabetic patient to a falling blood glucose concentration (4). Most notably, the onset of the catecholamine and sympathetic responses to hypoglycemia is significantly delayed, with reduced magnitude of these responses at any given glucose level (5).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia unawareness is associated with defects in the normal protective responses to a falling plasma glucose concentration (4). A greater degree of hypoglycemia is required to trigger hormonal and autonomic responses, and the magnitude of responses at any given glucose level is reduced (5).…”
mentioning
confidence: 99%
“…of hypoglycaemia in these patients [3], thus leading into a vicious cycle [4]. Although glucose represents the main fuel for the brain, it is also possible that under conditions of glucose shortage, brain function is maintained by the uptake of other energetic substrates.…”
mentioning
confidence: 99%
“…No study has found defects in counterregulatory responses to the hypoglycemia of human insulin comparable DIABETES, VOL. 44, MARCH 1995 to those found in other hypoglycemia-unaware groups (17)(18)(19).…”
mentioning
confidence: 71%